Impact of Ownership Structure and Corporate Governance on the Performance: A Case of Selected Banks in UAE - Mirchandani, Anita; Gupta, Namrata (International Journal of Economics and Financial Issues, 2018)
The purpose of this study is to analyze the intervening role of corporate governance in determining the impact of ownership structure on the performance of banks. A self-administered questionnaire has been used to collect the data. Descriptive Statistics, correlation analysis and regression model have been used to test the hypothesis. The result of the study shows that there is a significant relationship between corporate governance practices and bank’s performance. However, ownership structures do not have strong impact on the profitability of the banks. It is expected that the findings of this research paper would contribute to improve understanding about corporate governance practices in UAE banking sector. Keywords: Corporate Governance; Bank Performance; Ownership structure; Board size; Board composition; ROA; ROE JEL Classifications: G21; G32; G34